2019
DOI: 10.2147/jpr.s192246
|View full text |Cite
|
Sign up to set email alerts
|

<p>A systematic review of structural and functional MRI studies on pain catastrophizing</p>

Abstract: Objectives: Pain catastrophizing is reliably associated with pain reports during experimental pain in healthy, pain-free subjects and in people with chronic pain. It also correlates with self-reports of clinical pain intensity/severity in a variety of disorders characterized by chronic pain in adults, adolescents and children. However, processes, through which it exerts its effects are yet unclear. In this paper, our primary aim was to synthesize neuroimaging research to open a window to possible me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 114 publications
1
57
0
1
Order By: Relevance
“…Likewise, it has been suggested that the relationship between catastrophizing and heightened pain experience may be mediated through attentional processes, 41 which may explain why we observed neural correlations with PCS, but not between PCS and pain ratings per se. Furthermore, neuroimaging meta-analysis of pain catastrophizing 11 and instructed fear conditioning 29 report overlapping coactivation of the same regions that we observed in our whole-brain analysis to covary with increased PCS ratings in FMSs when stimulated with an identical mid-intensity painful pressure following green compared with red cue (ie, FM [P30green>P30red] × PCS) (Fig. 2 C), namely, in dACC/MCC, insula, bilateral thalamus, mPFC, putamen, superior, and middle parts of the temporal lobe.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, it has been suggested that the relationship between catastrophizing and heightened pain experience may be mediated through attentional processes, 41 which may explain why we observed neural correlations with PCS, but not between PCS and pain ratings per se. Furthermore, neuroimaging meta-analysis of pain catastrophizing 11 and instructed fear conditioning 29 report overlapping coactivation of the same regions that we observed in our whole-brain analysis to covary with increased PCS ratings in FMSs when stimulated with an identical mid-intensity painful pressure following green compared with red cue (ie, FM [P30green>P30red] × PCS) (Fig. 2 C), namely, in dACC/MCC, insula, bilateral thalamus, mPFC, putamen, superior, and middle parts of the temporal lobe.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Unfortunately, the mechanisms by which pain catastrophizing increases pain are currently poorly understood; however, accumulating evidence suggests they involve supraspinal processes (eg, attention deployment, salience detection, amplification of activity in pain-related brain regions), rather than activation of descending facilitatory pain controls. 28,29 Because NAs have a higher prevalence of pain symptoms and pain conditions than other US ethnic/racial groups, 5 investigating the contribution of psychological variables, especially pain catastrophizing, is highly relevant. In fact, given that the current study established the measurement invariance of the PCS across NAs and NHWs, the PCS was used in subsequent analyses to examine racial/ethnic differences in catastrophic thoughts in response to painful stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…is would in turn affect the postural control in patients with chronic LBP. Pain catastrophizing is characterized by enhanced pain perception, increased attention to noxious stimuli, the reinforcement of emotional responses to pain, or the weakened modulation of pain [46,47]. People with greater pain catastrophizing demonstrated increased activity in cortical areas that are related to the anticipation of pain (medial frontal cortex, cerebellum), attention to pain (dorsal anterior cingulate cortex, dorsolateral prefrontal cortex), and emotional aspects of pain (claustrum) [47].…”
Section: E Relationships Between Pain Catastrophizing Age Transversus Abdominis Activation and Static Posturalmentioning
confidence: 99%